2013
DOI: 10.1002/ccd.25283
|View full text |Cite
|
Sign up to set email alerts
|

The impact of regulatory approval and Medicare coverage on outcomes of carotid stenting

Abstract: Background Carotid artery stenting (CAS) was introduced in the United States nearly a decade ago as a novel treatment of severe carotid stenosis. Voluminous and high‐quality prospective data permit analysis of longitudinal trends in CAS outcomes. Methods Outcomes from all prospective trials with the Food and Drug Administration (FDA) oversight from 2000–2011 were reviewed, as were the subset of studies using a single CAS system. All studies shared common inclusion/exclusion criteria, endpoints, independent ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…7,8 This finding is consistent with a recent study that demonstrated a decline in periprocedural death and stroke rates in CAS after regulatory approval and Medicare coverage leading to increased operator experience and continued regulatory oversight. 34 Given that CAS is relatively novel technology in comparison with CEA, CAS has already undergone evolution in patient selection, technological advances, and procedural skills with a steep learning curve. Therefore, CAS is associated with significant improvement in outcomes over time as has been demonstrated in the CREST trial as well as the current study.…”
Section: Trends For Outcomes Of Cas and Cea 2001 To 2010mentioning
confidence: 99%
“…7,8 This finding is consistent with a recent study that demonstrated a decline in periprocedural death and stroke rates in CAS after regulatory approval and Medicare coverage leading to increased operator experience and continued regulatory oversight. 34 Given that CAS is relatively novel technology in comparison with CEA, CAS has already undergone evolution in patient selection, technological advances, and procedural skills with a steep learning curve. Therefore, CAS is associated with significant improvement in outcomes over time as has been demonstrated in the CREST trial as well as the current study.…”
Section: Trends For Outcomes Of Cas and Cea 2001 To 2010mentioning
confidence: 99%
“…Proximal protection devices, such as the GORE Flow Reversal System ® , Medtronic Mo.Ma ® device, and Silk Road ENROUTE ® system, are intended to prevent embolic particles from traveling to the brain by blocking or reversing flow to the cerebral circulation and aspirating or filtering these particles proximal to the treated lesion. Studies evaluating both distal and proximal embolic protection have been conducted over the past 10 years and have demonstrated that stroke rates have improved dramatically as techniques, patient selection, and technologies have been refined . The recent ROADSTER trial evaluating the ENROUTE ® system showed a 30‐day stroke rate of 1.4%, the lowest yet observed in a large U.S. pivotal carotid stenting study .…”
Section: Discussionmentioning
confidence: 99%
“…CREST lead‐in data demonstrated superior outcomes for operators from catheter‐based specialties such as interventional radiology and interventional cardiology compared with vascular surgery , but following conclusion of the training phase and accumulation of greater CAS experience, the quality gap between specialties narrowed . Recent analyses have demonstrated a marked improvement in CAS outcomes over the past decade, due to increasing access to and experience with CAS . Recognizing the importance of CAS experience, the NIH‐sponsored CREST‐2 trial has set the bar for operator experience higher than any prior trial.…”
Section: Physician Training and Credentialing In Casmentioning
confidence: 99%